The Development of Servant Leadership in Modern Organizational Management According to Good Governance Principles for Effectiveness of The Thailand Association of the Blind - Watcharachawakul, Sinlapachai; Kongyoungyune, Rungraditt; Lakul, Jitakorn; Channuwong, Sukhumpong (Journal of Neonatal Surgery, 2025)
The purposes of this research were: 1) To study servant leadership factors, modern organizational management factors, good governance management factors, and the overall service effectiveness of the Thailand Association of the Blind's executive committee; 2) To examine the relationships between servant leadership factors, modern organizational management factors, good governance management factors, and the overall service effectiveness of the Thailand Association of the Blind's executive committee; 3) To investigate the direct effects, indirect effects, and total effects of servant leadership factors, modern organizational management factors, and good governance management factors on the service effectiveness of the Thailand Association of the Blind's executive committee. The samples in this study consisted of 472 participants, including executives, vice presidents, committee members, and members of the Thailand Association of the Blind. Data was collected using questionnaires. Statistics employed in this study included percentage, mean, standard deviation, Pearson correlation coefficient, and path analysis. The research findings revealed that: 1) Servant leadership factors, modern organizational management factors, good governance management factors, and overall organizational effectiveness all had high mean values across all factors; 2) The relationships between servant leadership factors, modern organizational management factors, good governance management factors, and overall organizational effectiveness were statistically significant at the .01 level; 3) Servant leadership factors, modern organizational management factors, and good governance management factors had direct effects on organizational effectiveness at a statistically significant level of .01. Servant leadership factors and modern organizational management factors had direct effects on good governance management at a statistically significant level of .01. Servant leadership factors had indirect effects through good governance management factors on organizational effectiveness, with a positive total effect that was statistically significant at the .01 level (TE = 0.38, p < 0.01). Similarly, modern organizational management factors had indirect effects through good governance management factors on organizational effectiveness, with a positive total effect that was statistically significant at the .01 level (TE = 0.57, p < 0.01). Servant leadership factors, modern organizational management factors, and good governance management factors collectively explained and predicted 77% of organizational effectiveness factors (R² = 0.77).